Assessing healthcare service quality: a comparative study of patient treatment types - DonHee Lee; Kai K. Kim (International Journal of Quality Innovation, 2017)
The purpose of this study is to examine the effects of healthcare service quality (HEALTHQUAL) measurement items. First, the proposed measurement items for HEALTHQUAL were tested using data collected from a hospital in South Korea with more than 500 beds. The data set included 365 patients and 232 public respondents. ANOVA and t-tests were used to perform a comparative analysis of HEALTHQUAL measurement items among three patient treatment groups (inpatients, outpatients, and family members of patients in the emergency room) and between the patient and general public groups. The results indicated significant differences among measurement items of HEALTHQUAL depending on the type of patient treatment, while there were no significant differences among measurement items of HEALTHQUAL between patients and the public.
Keywords: 650; Healthcare service quality; HEALTHQUAL measurement items; Type of patient treatment